Effect of single amino acid substitution observed in cancer on Pim-1 kinase thermodynamic stability and structure - Lori, C; Lantella, A; Pasquo, A; Alexander, LT; Knapp, S; Chiaraluce, R; Consalvi, V (Public Library of Science, 2013)
Pim-1 kinase, a serine/threonine protein kinase encoded by the pim proto-oncogene, is involved in several signalling pathways such as the regulation of cell cycle progression and apoptosis. Many cancer types show high expression levels of Pim kinases and particularly Pim-1 has been linked to the initiation and progression of the malignant phenotype. In several cancer tissues somatic Pim-1 mutants have been identified. These natural variants are nonsynonymous single nucleotide polymorphisms, variations of a single nucleotide occurring in the coding region and leading to amino acid substitutions. In this study we investigated the effect of amino acid substitution on the structural stability and on the activity of Pim-1 kinase. We expressed and purified some of the mutants of Pim-1 kinase that are expressed in cancer tissues and reported in the single nucleotide polymorphisms database. The point mutations in the variants significantly affect the conformation of the native state of Pim-1. All the mutants, expressed as soluble recombinant proteins, show a decreased thermal and thermodynamic stability and a lower activation energy values for kinase activity. The decreased stability accompanied by an increased flexibility suggests that Pim-1 variants may be involved in a wider network of protein interactions. All mutants bound ATP and ATP mimetic inhibitors with comparable IC50 values suggesting that the studied Pim-1 kinase mutants can be efficiently targeted with inhibitors developed for the wild type protein.